INFLUENCE OF TRUST, SECURITY, AND RISK PERCEPTION REGARDING TO ONLINE CREDIT DECISIONS AT SHOPEE PAYLATER - Aditya Rizaldi, Kevin; Fakhri, Mahendra (The International Journal of Business Review (The Jobs Review), 2024)
The purpose of this study is to find out and analyze the influence of trust, security, and perceived risk on the decision to take Shopeepaylater online credit. The approach used is descriptive quantitative with the population being Shopeepaylater users and determining the sample using non-probability sampling. The samples obtained amounted to 400 with the characteristics of having used Shopeepaylater for 2 months. The results of the research data analysis show that trust, security, and perceptions simultaneously influence loyalty with a value of 9.027 and a significance of 0.004 0.005. Separately, trust has a significant influence on online credit decisions. Security has a significant influence on online credit decisions, and risk perception also influences online credit decisions at Shopeepaylater.